Pengaruh Model Problem Solving terhadap Prestasi Belajar Siswa Tema 5 Subtema 1 Keadaan Cuaca Kelas III SD Negeri 122332 Pematang Siantar - Kiki Leonaldo S; Lisbet N. Sihombing; Hetdy Sitio (Journal on Education, 2023)
This study aims to determine the effect of problem solving on student achievement in the thema 5 sub-thema 1 weather conditions class III in SD Negeri 122332 pematang siantar. This study held in SD Negeri 122332 p3matang siantar in Mei 2032. This research used is quantitative research using Quasi Eksperimental Design type Nonequivalent Control Group Design With the sample in the study is class students III C and III D as much 50 student. The variables in this study are picture media (x) and learning achievement (y). Methods of collecting data using tests. The data analysis technique used the normality test, homogeneity test, and hypothesis testing. based on the results of research that has been carried out for image media test data with a sample of 50 students, then the experimental class posttest scores with an average value of 43.20. posttest experimental class with an average value of 80.80. control class posttest with an average value of 40.00. control class posttest with an average value of 70.80.